Evaluation of neuroprotective and neurotoxic functions of different microglia phenotypes in Alzheimer’s disease onset and progression, using in vitro and in vivo models - Caldeira, Cláudia Alexandra Oliveira Lopes, 1973- (2020)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2017